Association between circulating tumor cells and peripheral blood monocytes in metastatic breast cancer. (August 2019) - De Giorgi, Ugo; Mego, Michal; Scarpi, Emanuela; Giordano, Antonio; Giuliano, Mario; Valero, Vicente; Alvarez, Ricardo H.; Ueno, Naoto T.; Cristofanilli, Massimo; Reuben, James M.
Background: We retrospectively evaluated the correlation between a baseline measurement of circulating tumor cells (CTCs) and inflammation-based scores in patients with metastatic breast cancer (MBC). Methods: The optimal value of inflammation-based scores as the neutrophil–lymphocyte ratio (NLR), platelet–lymphocyte ratio (PLR), monocyte–lymphocyte ratio (MLR) and systemic immune-inflammation index (SII) to predict survival was determined and compared with CTC <5 or ⩾5 per 7.5 ml of blood. Results: In the overall population of 516 women with MBC, CTCs correlated with peripheral blood monocytes ( p = 0.008) and neutrophils ( p = 0.038). In triple-negative tumors, CTCs correlated with monocyte count ( p = 0.009); in HER2+ tumors, CTCs correlated with neutrophil count ( p = 0.009), with a trend versus monocyte count ( p = 0.061), whereas no correlation was found in HER2– estrogen receptor-positive (ER+) tumors. In multivariate analysis only monocytes were associated with ⩾5 CTCs (OR = 2.72, 95% CI 1.09–6.80, p = 0.033). In multivariable analysis for predictors of overall survival, CTC (⩾5 versus <5), number of metastatic sites (>1 versus 1), tumor subtypes (triple-negative versus HER2– ER+ tumors) and MLR only remained significant. Conclusions: CTC and MLR are predictors of overall survival in MBC. CTC correlates with monocytes, in particular in triple-negative tumors.